Building Child-Friendly Education: Applying Appropriate Strategy to English Young Learners - Dewi, Isnain Evilina; Indarsih, Widayati (Indigenous, 2019)
The aim of the study is to investigate what strategies are appropriate and meaningful for young learners of English. The method used is qualitative descriptive. The data collection used for qualitative description are a semi-structured interview, observation, and analysis on lesson plans. The participants were an English teacher and 68 first graders. The findings showed that applying instructionbased strategy in the target language in which the learners responded by whole-body actions (physical actions) made young learners fun, dance with delight, act with joy, and finish off with big smiles. This strategy also encouraged young learners to learn English, especially that for vocabulary. The right-brain tool strategy made 41 young learners out of 68 or 60.29% participants were deeply engaged to class activity. It means the learners take full ownership of learning activity, show high levels of energy, and express a willingness to take part in activity. The strategy was effective and impressive that made young learners involved in meaningful activities which required repetition. In addition, the strategy could be applied to any class size. Furthermore, on the part of the teacher did not need to prepare a great deal or exceedingly.Keywords: young learners, vocabulary, instruction-based strategy, practical